Recuperação de áreas degradadas pela pecuária extensiva e agricultura itinerante com espécies florestais nativas da Amazônia - Lopes, Rosana Barbosa de Castro (Ciências de Florestas Tropicais - CFT, 2012)
This study examined the plantations to restore degraded areas by extensive cattle farming and shifting cultivation, with different silvicultural systems, with and without plowing and harrowing and with and without fertilization, using several native species of the Amazon. We evaluated the growth and survival and the mechanisms of natural regeneration as part of the recovery areas. The study was conducted in the Municipality of Presidente Figueiredo, January/2009 in the December /2010 in plantations with 8, 9 and 10 years old. The first area was used for extensive cattle raising, situated on the BR-174 highway, km 107, Fazenda Santa Claudia. The second was used for shifting cultivation and is located on highway Am - 240, km 28, Cristo Rei Community. Were evaluated survival, plant health and growth through the total height, DBH (1.30 m), DAS, crown area (m² ), degree of coverage and number of branches. Were also evaluated the mechanisms of natural regeneration in plots of 10 x 9 and 10 x 10 m for the study of the woody and shrub species, young regenerating individuals in plots of 1 x 1 m, and to the seed bank, in subplots of 0.25 x 0.25 m. For the seed rain were used collectors with circular frame with a diameter of 35 cm. The chemical and physical characterizations of the soils were made at a depth of 0-20 cm in each plantation. In the recovery of degraded areas by extensive cattle farming, the species Hymeneae courbaril, Carapa guianensis and Dipteryx odorata had the greatest growth and survival in soil plow and exhibiting resistance to competition with invasive species. The characterization of the mechanisms of natural regeneration, the species Vismia guianensis, Vismia sandwithii, Bellucia dichotoma, Casearia grandiflora and Miconia sp. were more prevalent in all areas with and without plowing. The variation in the physical texture of the soil was clayey to very clayey in areas with and without plowing. Changes in nutrient content varied with increases and decreases compared to 2002 values. In homogeneous plantations to recover degraded areas by shifting cultivation, the species Calophyllum brasiliense, Couepia longipendula, Anacardium giganteum, Swartzia corrugata showed higher growth and survival. The tree and shrub species Vismia guianensis , Vismia sandwithii, Bellucia dichotoma and Miconia sp. had a higher frequency in the mechanisms of natural regeneration in areas with and without fertilizer. At the age of 10 years planting, only there was change, in the classification of soil texture, from very clayey to silty clay. In enrichment planting of brushwood area with Cedrela odorata and Carapa guianenesis the growth was lower probably because of higher woody shading. In the areas of enrichment of brushwood, the natural regeneration with predominance of pioneer and secondary tree species, especially of the genera Vismia and Bellucia, were shading the rows. After the accidental fire, Cedrela odorata showed regrowth of the trunk, stem and root. In the seed bank in the two plantations, predominated basically the shrub species of the genus Miconia, Solanum and Trema. The Soil pH remained with high acidity, even after the accidental fire. For better development of pioneer specie Ochroma lagopus, used in mixed plantings for recovery of degraded areas, is necessary to better control of grasses and natural regeneration in areas used by cattle farming. In enrichment plantation in lines of brushwood, it is necessary to maintain the openness of the canopy to allow greater entry of light. In plantations to recover degraded areas with forest species monitoring is necessary to avoid herbivory, premature logging and accidental fire.
Keywords: Recuperação de áreas degradadas; Espécies florestais; Reflorestamento